Optimization of Computed Tomography Angiography Protocols for Follow-Up Type B Aortic Dissection Patients by Using 3D Printed Model - Wu, Chia-An; Squelch, Andrew; Jansen, Shirley; Sun, Zhonghua (MDPI AG, 2021)
Thoracic endovascular aortic repair (TEVAR) is a life-saving therapy for type B aortic dissection (TBAD). However, surveillance computed tomography (CT) scans in post-TEVAR patients are associated with high radiation dose, thus resulting in potential risk of radiation-induced malignancy. In this study, we developed a patient-specific three-dimensional (3D) printed phantom with stent grafts in situ, then scanned the phantom with different CT protocols to determine the optimal scanning parameters for post-treatment patients. The CT scans were conducted with different kVp and pitch values (80, 100, 120 kVp and pitch of 1.2, 1.5, 2.0, 2.5), resulting in a total of 12 datasets. Signal-to-noise ratio (SNR) was measured to determine and compare the image quality between different datasets. Results showed no significant differences in SNR between different kVp when the pitch value was 1.2. At low pitch values, a decrease in kVp from 120 to 80 led to a significant effective dose reduction by more than 20%. SNR decreased by 30% when pitch was increased from 1.2 to 2.5 at 80 kVp, and 20% at 120 kVp. In contrast, there was only a 3.9% decrease in SNR when kVp was reduced from 120 to 80 at pitch 1.2, and 15.9% at pitch 2.5. High pitch with 100 kVp can effectively reduce the dose while maintaining image quality.